Routledge handbook of critical international relations - Edkins, Jenny (Routledge handbooks, 2019)
Critical international relations is both firmly established and rapidly expanding, and this Handbook offers a wide-ranging survey of contemporary research. It affords insights into exciting developments, more challenging issues, and less prominent topics, examining debates around questions of imperialism, race, gender, ethics and aesthetics, and offering both an overview of the existing state of critical international politics and an agenda-setting collection that highlights emerging areas and fosters future research. Sections cover: critique and the discipline; relations beyond humanity; art and narrative; war, religion and security; otherness and diplomacy; spaces and times; resistance; and embodiment and intimacy. An international group of expert scholars, whose contributions are commissioned for the volume, provide chapters that facilitate teaching at advanced undergraduate and postgraduate level, inspire new generations of researchers in the field, and promote collaboration, cross-fertilisation and inspiration across sub-fields often treated separately, such as feminism, postcolonialism and poststructuralism. The volume sees these strands as complementary not contradictory, and emphasises their shared political goals, shared theoretical resources and complementary empirical practices. Each chapter offers specific, focused, in-depth analysis that complements and exemplifies the broader coverage, making this Routledge Handbook of Critical International Relations essential reading for all students and scholars of international relations.